Celecoxib as a neuroprotective agent in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Saxena, Anil Kumar; Mohd Noor, Mohd Fadly; A.Talib, Norlelawati (2013)
Objectives: Reduced cerebral blood flow (CBF)has been associated with neurodegenerative disorders. Since neuroinflammation is thought to play a significant role in chronic degenerative neurological disorders like Alzheimer's disease, the present study was planned to,assess the neuroprotective role of celecoxib in Alzheimer's model of rats(2VO). Methods:Experimentally,a condition of chronic cerebral hypoperfusion due to reduced CBF can be induced by permanent bilateral occlusion of common carotid arteries (2VO)in rats. After 1 week of acclimatization,fifteen Sprague Dawley rats weighing 200-250 g were equally divided into three groups. Group A served as - sham control, Group B - 2VO, and Group C - 2VO-C treated daily with celecoxib 50 mg/kg, orally following 2VO. On 8th week, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cells in the hippocampal CA-1 region were counted and hippocampal COX-2 mRNA expression and prostaglandin E2(PGE-2)levels were estimated. Results: There was a significant difference in neuronal cell death, increase in COX-2 mRNA expression and PGE-2 levels in 2VO group as compared to sham control group. In celecoxib-treated 2VO-C rats,the viable neuronal cell count of the hippocampal CA-l region was significantly higher as compared to the untreated 2VO group. The hippocampal COX-2 mRNA expression and hippocampal PGE-2 levels were found to be significantly lower in the celecoxib-treated 2VO rats as compared to untreated 2VO rats. Conclusions: The results indicate that celecoxib could be successfully used in the management of Alzheimer's disease. No conflict of interest.